Two ways of experimental infection of Ixodes ricinus ticks (Acari: Ixodidae) with spirochetes of Borrelia burgdorferi sensu lato complex - Fišerová, Lenka; Černá, Kateřina; Horká, Helena; Kopecký, Jan (Folia parasitologica, 2008)
A previously reported procedure for the introduction of Borrelia spirochetes into tick larvae by immersion in a suspension of spirochetes was tested on Ixodes ricinus (L.) ticks and three of the most medically important European Borrelia genomic species, B. burgdorferi sensu stricto, B. garinii and B. afzelii. The procedure was compared with “classical” infection of nymphs by feeding on infected mice. Both methods yielded comparable results (infection rate 44–65%) with the exception of B. afzelii, which produced better results using the immersion method (44%) compared with feeding on infected mice (16%). Nymphs infected by the immersion method at the larval stage were able to transmit the infection to naive mice as shown by serology and PCR detection of spirochetal DNA in organs. The immersion method is faster than feeding on infected mice and provides more reproducible conditions for infection. It can be exploited for studies on both pathogen transmission and Borrelia-vector interactions.
Keywords: Borrelia burgdorferi komplex; lymeská nemoc; polymerázová řetězová reakce; klíště; Lyme Disease; Nymph; Borrelia burgdorferi Group; ELISA; DNA, Bacterial; nymfa; DNA bakterií; larva; Animals; Enzyme-Linked Immunosorbent Assay; ženské pohlaví; zvířata; myši; protilátky bakteriální; Ixodes; Polymerase Chain Reaction; Larva; Mice; Female; Antibodies, Bacterial